DNA Methylation of FKBP5 as Predictor of Overall Survival in Malignant Pleural Mesothelioma - Cugliari, Giovanni (Cancers (Basel), 2020)
SIMPLE SUMMARY: Our study is the first one to investigate DNA methylation changes in white blood cells (WBCs) from easily accessible peripheral blood as malignant pleural mesothelioma (MPM) survival biomarker. The Cox proportional hazards regression model highlighted that the methylation status of the CpG dinucleotide cg03546163 is an independent marker of prognosis in MPM patients with a better performance than traditional inflammation-based scores such as lymphocyte-to-monocyte ratio (LMR). Biological validation and replication showed that epigenetic changes at the FKBP5 gene were robustly associated with overall survival (OS) in MPM cases. The identification of simple and valuable prognostic markers for MPM will enable clinicians to select patients who are most likely to benefit from aggressive therapies and avoid subjecting non-responder patients to ineffective treatment. ABSTRACT: Malignant pleural mesothelioma (MPM) is an aggressive tumor with median survival of 12 months and limited effective treatments. The scope of this study was to study the relationship between blood DNA methylation (DNAm) and overall survival (OS) aiming at a noninvasive prognostic test. We investigated a cohort of 159 incident asbestos exposed MPM cases enrolled in an Italian area with high incidence of mesothelioma. Considering 12 months as a cut-off for OS, epigenome-wide association study (EWAS) revealed statistically significant (p value = 7.7 × 10(−9)) OS-related differential methylation of a single-CpG (cg03546163), located in the 5′UTR region of the FKBP5 gene. This is an independent marker of prognosis in MPM patients with a better performance than traditional inflammation-based scores such as lymphocyte-to-monocyte ratio (LMR). Cases with DNAm < 0.45 at the cg03546163 had significantly poor survival compared with those showing DNAm ≥ 0.45 (mean: 243 versus 534 days; p value< 0.001). Epigenetic changes at the FKBP5 gene were robustly associated with OS in MPM cases. Our results showed that blood DNA methylation levels could be promising and dynamic prognostic biomarkers in MPM.